Modified transumbilical laparoscopic cholecystectomy: Double-incision, triple-port access. Issue 2 (April 2012) - Zhang, Hai-Feng; Lu, Chun-Lei; Gao, Ying; Chen, Dong-Feng; Wang, Wei-Jia
Abstract Transumbilical laparoscopic cholecystectomy has been increasingly performed in recent years, using special access devices and instruments through one incision in the umbilicus. We have modified the technique by using a two-incision triple-port access approach and conventional laparoscopic instruments. A total of 52 patients accepted the modified transumbilical laparoscopic cholecystectomy, and all the procedures were completed successfully. The operative time was 150 minutes for the first case, 100 minutes and 90 minutes for the second and third cases, and an average of 50 ± 14 minutes for the following 49 cases. All patients were discharged on post-operative day 3. No complications were observed during a follow-up of at least three months. The umbilical incisions were nearly invisible, and all patients were satisfied with the abdominal cosmetic results.In conclusion, transumbilical laparoscopic cholecystectomy using a double-incision triple-port access approach and conventional laparoscopic instruments as described in this study is safe and feasible, and it reduces the conflict of instruments without using special devices.